Kepemimpinan Transformasional Kuwu Desa Ciparay Leuwimunding Majalengka - Habib Abdul Muhyi; Ahmad Munajim (IAI Bunga Bangsa Cirebon, 2019)
This study deepens Burns's concept of transformational leadership. Transformational leadership is characterized as a leader who focuses on achieving changes in the values, beliefs, attitudes, behavior, emotional, and needs of subordinates for the better in the future. According to Danim, Bass, O'Leary, Robbins and Judge, transformational leaders are leaders who inspire their followers to put their personal interests aside for the good of the organization and are able to have a tremendous influence on their followers. This research will deepen the characteristics of transformational leadership based on Robbins and Judge. Meanwhile, the independent position of this research is emphasized on the inspiration of the kuwu to play its role in policy making. The object of this research is the Inspiration of Kuwu Ciparay, Leuwimunding Subdistrict, Majalengka Regency, the reason for determining the place is because the leading village is 1 (one) in Majalengka Regency and 4 (four) in West Java. Judging from the object, the researcher used a qualitative research type with a cultural interpretation approach. While the method used is descriptive method and ex post facto. Collecting data through in-depth interviews, observation and documentation. From the data collected, the authors then categorize and reduce data, display and classify data, interpretation and verification, and generalize. The findings show that Kuwu Ciparay's efforts in determining policies, namely the ideal influence of the Ciparay village kuwu in creating and implementing a vision and mission in accordance with community expectations, protecting citizens and being transparent are proven by issuing several Perdes and Perkades. Motivating Inspirational which is carried out by inviting all elements of society to deliberate consensus in the implementation of intellectual stimulation can stimulate the growth of innovation, creativity and new ways of solving problems by presenting all parties, in implementing individual considerations, Kuwu always advocates for the community in any field, including unnecessary funding. relying on village funds, even from individuals. Efforts made by the Kuwu in village management include providing excellent service, equitable distribution of asset auction results and plans to build hospitals and swimming pools to improve the local budget and economy. Abstrak Penelitian ini memperdalam konsep Burns tentang kepemimpinan transformasional. Kepemimpinan transformasional dicirikan sebagai pemimpin yang berfokus pada pencapaian perubahan nilai-nilai, kepercayaan, sikap, perilaku, emosional, dan kebutuhan bawahan menuju perubahan yang lebih baik di masa depan. Menurut Danim, Bass, O’Leary, Robbins dan Judge pemimpin transformasional adalah pemimpin yang menginspirasi para pengikutnya untuk menyampingkan kepentingan pribadi mereka demi kebaikan organisasi dan mampu memiliki pengaruh yang luar biasa pada diri para pengikutnya. Penelitian ini akan memperdalam ciri-ciri kepemimpinan transformasional berdasarkan Robbins dan Judge. Adapun, posisi independen penelitian ini ditekankan pada inspirasi kuwu menjalankan perannya di dalam penentuan kebijakan. Objek penelitian ini adalah Inspirasi Kuwu Ciparay Kecamatan Leuwimunding Kabupaten Majalengka, alasan penentuan tempat tersebut dikarenakan Desa unggulan jauara 1 (satu) di Kabupaten Majalengka dan jauara 4 (empat) di Jawa Barat. Dilihat dari objeknya maka peneliti menggunakan jenis penelitian kualitatif dengan pendekatan penafsiran budaya. Sedangkan metode yang digunakan adalah Metode deskriptif dan ex post Facto. Pengumpulan data melalui wawancara mendalam, observasi dan dokumentasi. Dari data terkumpul kemudian penulis melakukan katagorisasi dan reduksi data, display dan klasifikasi data, interprestasi dan verifikasi, serta generalisasi. Temuan menujukkan bahwa upaya Kuwu Ciparay dalam menetukan kebijakan yaitu Pengaruh ideal kuwu Desa Ciparay dalam membuat dan melaksanakan Visi dan Misi sesuai dengan harapan masyakat, mengayomi warga dan transparan dibuktikan dengan menerbitkan beberapa Perdes dan Perkades. Memotivasi Inspirasional yang dilakukan dengan mengundang semua elemen masyarakat untuk musyawarah mufakat dalam pelaksanaan stimulasi intelektual kuwu dapat merangsang tumbuhnya inovasi, kreatifitas dan cara-cara baru dalam menyelesaikan masalah dengan menghadirkan semua fihak, dalam implementasi pertimbangan individual kuwu selalu mengadvokasi masyarakat dibidang apapun termasuk pendanaan tidak mesti mengandalkan dana desa bahkan dari individu.Upaya yang dilakukan kuwu dalam pengelolaan desa yakni memberikan service excellent, pemerataan hasil lelang asset dan rencana membangun Rumah sakit dan Kolam Renang dalam meningkatkan APBDes dan Ekonomi warga.